The impact of conditional factors on the performance of accounting information systems and their reflection on the quality of information (A field study in a sample of commercial banks in Sulaymaniyah Governorate) - Hardi Azad Omar (The Scientific Journal of Cihan University– Sulaimaniya, 2019)
The development of applying information systems in the firms and the banking sector is the main fundamental to provide appropriate and reliable information at the lowest possible cost for the appropriate decision-making process. Conditional factors are represented by (work environment, technology, management and the size of the firms) which have a clear impact on the design and improvement of the accounting information system performance. This study aims to analysis the conditional factors and their impact on the design of the accounting information system and its reflection on the quality of accounting information, to insure and provide information for decision makers which contribute to the process of building of accounting information system. To achieve this objective, the (Descriptive-Analytical) approach, through the collection of data and information from the questionnaires, which are distributed among (70) employees working on a sample of commercial banks in the Sulaimani province, but only (61 response) was recovered and used as a basic of study. Finally, the study has revealed a set of conclusions, including that the conditional factors represented in (work environment, technology, management and the size of the firms) have the impact on the performance of the accounting information system, and its impact on quality of accounting information varies from each individual factor. At the end, based on the conclusions of the study, some recommendation has been provided, including should banks seek to build and design information systems or that require reviewing their existing systems to study the relationship between the conditional factors and the accounting information system. This is to guide and help management decision makers (list and continues) in the process of obtaining qualitative accounting information.